REDUKSI KANDUNGAN AFLATOKSIN B1 (AFB1) PADA PEMBUATAN KACANG TELUR MELALUI PEREBUSAN DALAM LARUTAN KAPUR (REDUCTION OF AFLATOXIN B1 (AFB1) CONTENT IN THE EGG PEANUT BY BOILLING IN LIME SOLUTION) - Yuliana Tandi Rubak; Suryana Purawisastra (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2011)
ABSTRAK Latar belakang: Efek berbahaya dari aflatoksin B1 bagi manusia adalah toksisitasnya sebagai senyawa karsinogenik. Toksin ini diproduksi oleh Aspergillus flavus, yang biasanya tumbuh pada serealia dan kacang-kacangan. Akibatnya serealia dan kacang-kacangan tersebut serta produknya bisa terkontaminasi oleh toksin ini. Kacang telur merupakan salah satu produk kacang tanah yang banyak dikonsumsi. Karena itu, kacang telur harus bebas toksin. Menurut informasi pustaka, salah satu cara untuk menghilangkan toksin ini adalah modifikasi proses pembuatan kacang telur. Artikel ini menyajikan hasil penelitian untuk menghilangkan aflatoksin kacang telur melalui perendaman bahan baku kacang tanah dalam larutan kapur 0,5 persen dan 1 persen selama 10 menit. Metodologi: Membuat dua jenis produk kacang telur, satu produk berbahan baku kacang yang telah dikontaminasi aflatoksin dan satu produk lagi berbahan baku kacang utuh tidak terkontaminasi aflatoksin. Produk pertama untuk menguji pengaruh perebusan dalam larutan kapur terhadap kandungan aflatoksin. Sedangan produk kedua untuk menguji pengaruh perebusan dalam larutan kapur terhadap cita rasa.Kedua produk dibuat melalui proses yang sama, bahan kacang mendapat perlakukan perendaman dalam larutan kapur konsentrasi 0,5 persen dan 1,5 persen selama 10 menit, kemudian dilanjutkkan dengan proses seperti umumnya membuat kacang telur. Kandungan aflatoksin dianalisis dengan metoda ELISA (Enzyme Linked Immunosorbent Assay). ABSTRACT Background: The harmful effect of aflatoxin B1 for human being because of its toxicity, as carcinogenic agent. The toxin is produced by the Aspergillus flavus which usually grows in grain and nuts. As the result that the grain, nuts and their product contaminated by the toxin.  Egg peanut is one of peanut products which are widely consumed by the peoples. Consequently the egg peanut should be not containing the toxin. The modification of process of making peanut is one way to eliminate the toxin. Objectives: To eliminate the aflatoksin B1 content in the product of egg peanut through the preparation of raw peanuts by boiling the peanut in the boiled lime solution. The concentration of the lime solution in this research was 0.5 percent, and 1.5 percent for 10 minutes. Methods: There were two kinds of peanut egg, one was made from the raw peanuts which were already contaminated by the aflatoxin, and another one from the raw peanuts was not contaminated. The first product was to observe the influenced of boiling in the lime solution of peanuts to the content of aflatoxin. The second product was to observe the influenced of boiling in the lime solution of peanuts to the sensory of peanut eggs. Aflatoxin analysis was carried out by ELISA (Enzyme Linked Immunosorbent Assay). Results: The result of research showed that the preparation of the raw peanuts by boiling in lime solution was able to reduce the content of aflatoxin in peanut eggs. The percentage of reduction was increased by increasing the concentration of lime solution. In this study, the reduction of aflatoxin for the peanuts which was boiled in the 0.5 percent of lime solution was 27.8 percent. The reduction was increased becoming 29.5 percent when the peanuts boiled in the 1.5 percent of lime solution. The roasting of the peanut increased 44 percent the reduction of aflatoxin content. Conclusion: The modification process of making the egg peanut by boiling in lime solution could reduce the aflatoxin content, whereas the sensory of peanuts was not affected. The reduction content of aflatoxin was depending on the concentration of lime solution. [Penel Gizi Makan 2011, 34(1): 21-28] Keywords: Aflatoxin B1, peanuts, eggs peanut, lime solution, ELISA